Emotional competences as predictors of psychological wellbeing and quality of life of supplementary grandparents caregivers - Galarraga, Leyre; Noriega, Cristina; Pérez-Rojo, Gema; López, Javier (Frontiers in Psychology, 2024)
Introduction Grandparents are increasingly becoming key figures in the supplementary care of grandchildren. Based on the Resilience Model of Family Stress, Adjustment and Adaptation, the present study aims to analyze the emotional competences that canpl predict higher levels of psychological wellbeing and quality of life in supplementary grandparents caregivers. Methods A sample of 270 supplementary grandparents caregivers living in Spain participated. Most participants were women (71.1%), and the mean age was 67.83 years (SD = 6.26). Most participants were occasional caregivers, that is, they care for less than 10 h per week (76.3%). We conducted hierarchical multiple regression analysis, one for psychological wellbeing and the other for quality of life. Results The regression model for psychological wellbeing identified that age, management of caregiving stress, self-confidence in the caregiving role, management of work-life balance difficulties and emotional self-regulation explained 32.8% of its variance. The regression model for quality of life showed that age, type of grandparent caregiver, management of caregiving stress, management of work-life balance difficulties and emotional self-regulation explained 31.2% of its variance. Conclusion This study focuses on supplementary grandparents caregivers, whereas literature has tended to look at primary grandparents caregivers. The results highlight the role of emotional competences as predictors of supplementary grandparents caregivers’ psychological wellbeing and quality of life, overcoming the usual tendency in the literature to focus on the negative consequences of grandparents caregiving for grandchildren, and emphasizing the competences that grandparents have to cope with this care in a satisfactory way, which, moreover, can be trained.